Positivisms and traditionalisms in Colombia: remarks to reopen an archived file - Saldarriaga Vélez, Oscar (Estudios de Filosofía, 2008)
Given the kind of closure to which the stories of ideas in Colombia have led to the file on the relations between positivisms and traditionalisms, and given the need to construct criteria for the recognition of "positivism", I believe it is necessary to do a preliminary work of reproblematization of these relationships at the global level, using the contributions of European and Colombian historians and philosophers, to which I will dedicate the following pages. What is surprising in the most recent literature on the relations between traditionalisms and positivisms is the indication of a series of singular kinships, contrary to what we have usually thought. I would then like to review those relationships, and then draw some conclusions that allow us to reorient our research. [Fragment]